Self-inflicted penetrating cardiac injury. Two different surgical approaches - Stojiljković, Vladimir; Zivic, Sasa; Peric, Dejan; Kamenov, Aleksandar; Paunovic, Nenad; Gmijović, Marko; Milic, Dragan (Acta medicae Medianae, 2020)
Penetrating cardiac injuries  represent a great challenge for the surgeon because of their lethality. It is estimated that more than 90% of mortality happens before the patient reaches the hospital and survival after stab wounds to the heart is about 50 % as opposed to 11 % for gunshot wounds.A 58-year-old hemodynamically unstable male was brought to the ED with  two stab wounds to the left chest. Two surgical approaches were applied to treat the injury. First urgent left antero-lateral thoracotomy with left ventricle suture repair was performed. Few hours later due to massive bleeding and hemodynamic instability left ventricle repair through a median sternotomy with extracorporeal circulation and cardiac arrest was performed.Heart injuries can be treated with two surgical approaches. Left thoracotomy can be feasibly applied in emergency department but median sternotomy provides better access to heart and all important cardiovascular structures.Prompt and early diagnosis associated with a well-trained surgical team can be crucial in the management of life-threatening cardiac injuries.
Keywords: penetrating, heart, injury